Termitomyces acriumbonatus sp. nov. (Lyophyllaceae, Agaricales) from Pakistan - Usman, Muhammad; Khalid, Abdul Nasir (Phytotaxa, 2020)
Four Termitomyces samples were collected in fungal surveys during 2016–2017 at Pabbi Forest Park, Punjab, Pakistan. Detailed morphological examination showed the four collections represent a new species. The phylogenetic analyses of Internal Transcribed Spacer (ITS) and Larger Sub-Unit (LSU) genes also supported the morphology to establish the new species which we describe and illustrate in this paper. The new species, Termitomyces acriumbonatus, is characterized by a small pileus 15–30 mm diam., with pointed grayish brown perforatium, cylindrical smooth stipe, and ellipsoid, 6.1−8.7 × 4.5–6.5 μm sized basidiospores.